Evaluation of Mapping Discharge Summary CDA Document to FHIR - Kimura, E; Nakayama, M; Kaminaka, S; Furuzono, T (Japan Journal of Medical Informatics, 2019)
It has been pointed out that when medical information written in conformity with a specific information model is converted to another information model, information loss or malformation usually occurs. Fast Healthcare Interoperability Resources (FHIR) adopts the different design scheme from that of Clinical Document Architecture (CDA) and expresses medical information by combining resources, which are modularized components. The FHIR developer claims that the FHIR can be the successor standard to HL7 2.x and CDA, and that we can convert legacy data while inheriting the characteristics of these standards, and that yet it can benefit from modern information technology. We verified this assertion through the porting of CDA-based discharge summary to FHIR. As far as this verification is concerned, it was confirmed that CDA document information could be ported to documents composed of FHIR resources with almost no information loss. Also, by being conscious of profile compliance, it is expected to promote the restructuring of internal information model in electronic medical records system and becomes a driving force for mutual information sharing between different healthcare settings.